Pre-Service Teacher’s Beliefs and Knowledge about Mathematics - Muhtarom, Muhtarom; Happy, Nurina; Nursyahidah, Farida; Casanova, Anriany (Al-Jabar: Jurnal Pendidikan Matematika, 2019)
This research describes the knowledge and beliefs of pre-service teachers about mathematics. Data collection of this research using written test of 143 mathematics pre-service teachers who have taken six semesters at Universitas PGRI Semarang, and interviewing of three pre-service teachers who are not consistent between knowledge and belief. The data are presented in the form of descriptive quantitative and analyzed qualitatively, including data reduction, data display, and conclusions drawing/verification. The results show that most of the knowledge of pre-service teachers are consistent with their beliefs. It is indicated that pre-service teachers’ knowledge has been internalized into a strong belief that affect their words and behaviors. The belief of almost half of pre-service teachers who become respondents changes because of lecturer activity effect. It can say that belief changes at any time, both the process of alteration and the formation of new beliefs as well as the reinforcement of the beliefs they have.